Characteristics of Heat Waves From a Disaster Perspective - Do-Woo Kim; Chaeyoung Kwon; Jineun Kim; Jong-Seol Lee (Korean Society for Preventive Medicine, 2020)
In September 2018, heat waves were declared to be a type of natural disaster by the Framework Act on the Management of Disasters and Safety. The present study examined the characteristics of heat waves from the perspectives of meteorological phenomena and health damage. The government's efforts to minimize the damages incurred by heat waves are summarized chronologically. Furthermore, various issues pertaining to heat waves that are being raised in our society despite the government's efforts are summarized by analyzing big data derived from reported news and academic articles.